Peningkatan Kemampuan Sains Anak melalui Kegiatan Merangkai Lampu di Taman Kanak-kanak - Afrianti, Neneng; Ismet, Syarul (Penerbit Aksara Rentaka Siar (ARS), 2019)
This study aims to improve the scientific ability of early childhood and Taman Kanak-kanak plus Marhamah the Tabing Padang. With total subject of 13 childrend, 7 boys and 6 gilrs. This research was conducted in semester 1 of the school ear 2018-2019. This type of research is classroom action research consisting of 3 there was an increase in children’s scientific abilities through lighting activities eith an average of %. After reflaction improvements were made to cycle was an increase in children’s scientific abilities reaching %. There result indicate the achiement of minimum complateness criteria it can be concluded that the activity of assembling lights can improve early childhood scientific abilities.